2017
DOI: 10.1038/srep45391
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature three-photon pumped CH3NH3PbBr3 perovskite microlasers

Abstract: Hybrid lead halide perovskites have made great strides in next-generation light-harvesting and light emitting devices. Recently, they have also shown great potentials in nonlinear optical materials. Two-photon absorption and two-photon light emission have been thoroughly studied in past two years. However, the three-photon processes are rarely explored, especially for the laser emissions. Here we synthesized high quality CH3NH3PbBr3 perovskite microstructures with solution processed precipitation method and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 30 publications
(45 reference statements)
2
42
0
Order By: Relevance
“…Overall, the β values of TCMHP film are significantly higher than those of MAPbI 3 film and an order of magnitude higher near to the peak intensity of 35 GW cm −2 . While we could not observe the 3PA response for MAPbI 3 film, the obtained γ values of TCMHP film for each intensity are much larger than those of other perovskite film, micro‐/nanocrystals, and single crystal 15,16,56–60. The β and γ values of various types of perovskite materials reported in previous literatures and current study are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…Overall, the β values of TCMHP film are significantly higher than those of MAPbI 3 film and an order of magnitude higher near to the peak intensity of 35 GW cm −2 . While we could not observe the 3PA response for MAPbI 3 film, the obtained γ values of TCMHP film for each intensity are much larger than those of other perovskite film, micro‐/nanocrystals, and single crystal 15,16,56–60. The β and γ values of various types of perovskite materials reported in previous literatures and current study are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 49%
“…The halide perovskites also exhibit strong nonlinear optical (NLO) responses, thus opening up possibilities for optoelectronic device applications 10–14. For instance, organic–inorganic hybrid perovskites with large two‐ and three‐photon absorption (2PA, 3PA) properties14–16 can be utilized in applications such as bioimaging,17,18 optical limiting,19 optical sensor protection,20 and optical data storage 21…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With one‐photon pumping, the charge carriers are predominantly injected near the microcrystal surface due to the large absorption coefficient. The surface charge carrier trapping could easily dominate over other influences in determine the lasing threshold (this typically happened in the size of few micrometers) . Additionally, both of the previously discussed Q factor and light confinement should increase with cavity length.…”
Section: Size Dependence Lasing In Perovskite Micro‐/nanostructuresmentioning
confidence: 99%
“…Gao et al demonstrated that the single crystal MAPbBr 3 perovskite microstructures displayed the three‐photon process, which showed the band‐to‐band PL at 540 nm when they are pumped with 1240 nm lasers, and the three‐photon‐absorption coefficient as large as γ = 2.26 × 10 −5 cm 3 GW −2 . Base on it, the first report about experimental WGM microlasers have been achieved from MAPbBr 3 perovskites (Figure e) . Different from other works, Tang et al also developed a new type of all‐organic CsPb 2 Br 5 perovskite and demonstrated large optical gain and two‐photon pumped lasing emission in these microplate which is related to its unique spatially distinguished valence/conduction band edge states originating from the intrinsic sandwiched structure .…”
Section: Perovskite Laser Applicationsmentioning
confidence: 99%